THE QUR’ANIC COMMUNICATION ETHICS IN SOCIAL MEDIA - Faizatun Khasanah (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
The politicization of religion in virtual sphere has increased significantly during the election. Political symbols are mobilized to shape public opinion, especially in social media. As a result, social media has become an arena for candidates to contest and get votes as well as political supports. This contestation involves black campaign and hoax. Using a philosophical analysis this article examines ethical values in social media based on Al-Hujarât verses. This article shows that the ethics of communication as mentioned in al-Hujarât verses describe two important points namely the producer of news (communicator) and as the news reader (communicant). Al-Hujarât explains that a communicator has to convey messages in a very sophisticated ways, avoid lowering others, dividing and ruling, circulating hoax, and adjusted to the interlocutor. As communicants need to instill critical thoughts and clarification (tabayyun) towards the truth of the news content.